Advanced Nonflammable Localized High‐Concentration Electrolyte For High Energy Density Lithium Battery. Issue 4 (15th March 2022) - Jia, Mengmin; Zhang, Chi; Guo, Yawei; Peng, Linshan; Zhang, Xiaoyan; Qian, Weiwei; Zhang, Lan; Zhang, Suojiang
Abstract : The key to realize long‐life high energy density lithium batteries is to exploit functional electrolytes capable of stabilizing both high voltage cathode and lithium anode. The emergence of localized high‐concentration electrolytes (LHCEs) shows great promise for ameliorating the above‐mentioned interfacial issues. In this work, a lithium difluoro(oxalate)borate (LiDFOB) based nonflammable dual‐anion LHCE is designed and prepared. Dissolving in the mixture of trimethyl phosphate (TMP) /1, 1, 2, 2‐tetrafluoroethyl‐2, 2, 3, 3‐tetrafluoropropylether (D2 ), the continuously consumption of LiDFOB is suppressed by simply introducing lithium nitrate (LiNO3 ). Meantime, as most of the TMP molecular are coordinated with Li +, the electrolyte does not show incompatibility issue between neither metal lithium nor graphite anode. Therefore, it demonstrates excellent capability in stabilizing the interface of Ni‐rich cathode and regulating lithium deposition morphology. The Li||LiNi0.87 Co0.08 Mn0.05 O2 (NCM87) batteries exhibit high capacity retention of more than 90% after 200 cycles even under the high cutoff voltage of 4.5 V, 1 C rate. This study offers a prospective method to develop safe electrolytes suitable for high voltage applications, thus providing higher energy densities. Abstract : A dual‐anion phosphate‐based nonflammable electrolyte was designed and prepared. Taking advantage of synergistic effect of LiDFOB and LiNO3, the electrolyte shows good compatibility with both high voltage cathode and lithium metal anode; meantime, the continuous consumption of LiDFOB is restrained by LiNO3 . Thus, it shows impressive capacity retention of 97.8% after 200 cycles under high cutoff voltage of 4.5 V.